Developing a blood glucose meter-based method for the rapid detection of lactose in dairy ingredients - Wagner, Caleb (Kansas State University, 2019)
Lactose is an important nutritional, functional, and economical constituent of dairy ingredients. The lactose content of a dairy ingredient can often be directly associated with that ingredients value, shelf life, and finished application use. Lactose assays commonly employed by the dairy ingredients industry are time-consuming and require sophisticated equipment or trained staff to perform. A blood glucose meter (BGM) biosensor based lactose analysis has been developed for milk, but has not been documented for proper use with more compositionally variable systems such as dairy ingredients. The proposed BGM lactose analysis method involves diluting a sample to an appropriate level with buffer, adding lactase enzyme, incubating at 40°C for 15 minutes, and measuring the resulting glucose content with the BGM. A calibration curve developed between the known lactose concentration and BGM reading is used to quantify lactose in unknown samples. The objective of this study was to evaluate the BGM lactose analysis method in whey- and skim milk-derived (WD and SMD, respectively) ingredients. Measurement interferents such as solution pH and different types or amounts of non-lactose solids present in the measurement background were investigated for their impact on BGM output bias; it was found that measurement solution pH must be between 6.7 -7.0, and that calibration procedures must be designed to correct for large differences in non-lactose solids that may be present when measuring different materials. A standardized calibration procedure was then developed and verified by measuring the lactose content of model WD and SMD ingredient dilutions using the proposed BGM method and an enzymatic spectrophotometric absorbance (EZA) reference method. Lactose in 15 dried commercial dairy ingredients of both WD and SMD type over a broad range of lactose contents (0.01-81.9% lactose as-is) was then quantified using the BGM method and EZA reference method. When the correct calibration procedure and an optimal BGM-brand are employed, excellent BGM assay accuracy was obtained for the commercial samples, with an average absolute percent bias difference of <5% noted between the BGM method and EZA reference method results. Furthermore, an average percent coefficient of variation of <3% between duplicate measurements for the BGM method in these commercial samples indicates excellent method precision. Overall, the BGM method is a promising tool for rapid, low-cost analysis of lactose in dairy ingredients for purposes such as quality control, process development, or ingredient standardization.
Keywords: Dairy ingredients; Blood glucose meter; Rapid method; BiosensorLactose analysis